Comparative Exercise Physiology: A Worldwide Goal - Gomes Ferreira Padilha, Felipe (Journal of Sports and Exercise Medicine, 2018)
This perspective advocates comparative exercise physiology across species to advance understanding of performance, adaptation, and health applications.
Keywords: Comparative Exercise Physiology; Exercise Physiology; Performance; Adaptation; Health